Impact of HEXACO Personality Factors on Consumer Video Game Engagement: A Study on eSports - Abbasi, Amir Z.; Nisar, Saima; Rehman, Umair; Ting, Ding H. (Frontiers in Psychology, 2020)
This paper aims to uncover novel insights into personality factors and consumer video game engagement modelling. This research empirically validates the role of specific HEXACO personality factors that foster consumer engagement (CE) in eSports users. Using a survey-based approach, we incorporated the HEXACO 60-items and consumer videogame engagement scales for data collection. Data were collected from eSports users, with 250 valid responses. WarpPLS 6.0 was used for PLS-SEM analyses comprising measurement and structural model assessment. The results showed that the reflective measurement model is reliable and sound. Whereas, the second-order formative measurement model also meets the criteria of indicator weights and Collinearity values (VIF). The results based on the structural model indicate that openness-to-experience, extraversion, agreeableness, and conscientiousness positively predict consumer engagement in eSports. This paper is first among others who conceptualizes and validates the HEXACO personality traits as a reflective formative model using the hierarchical component model (HCM) approach. The research model carries the explanatory capacity for consumer engagement in eSports concerning personality dimensions as indicated by the HEXACO model. It highlights the potential benefits of such research especially to marketers who could potentially employ personality modelling to develop tailored strategies to increase CE in video games.